The political philosophy of Michel Foucault [ - Kelly, Mark G. E. (Routledge studies in social and political thought, 2009)
Presents Michel Foucault's political and philosophical thought across his career. This book argues, in the areas of epistemology, power, subjectivity, resistance, politics, and ethics, that Foucault's